Surveying clinician perceptions of risk assessment and management practices in mental health service provision. (April 2015) - Wand, Timothy; Isobel, Sophie; Derrick, Kate
Objectives: This study aimed to survey multidisciplinary mental health staff on their perceptions of risk assessment and management practices in a local health district in Sydney. Methods: The research team developed the risk assessment and management survey (RAMS) which was distributed to staff across the district from November 2013 to January 2014. Results: A total of 340 RAMS were distributed and 164 were returned (48% response rate). There was considerable agreement that risk assessment and management is essential to maintaining safety and delivering good mental health care, and respondents reported high levels of confidence in their judgement when carrying out such practices. Respondents identified organisational pressure in relation to risk assessment and management but also felt supported. However, 65% of respondents considered that there 'is good evidence that risk assessment and management practices are effective in reducing risk in mental health care', when this is not the case. Conclusion: The confidence that clinicians placed in risk assessment and management practices (despite an absence of evidence) is disconcerting. Given the dominance of risk assessment and management, health services mandating such practices have a duty to inform employees of the current evidence base for this approach in reducing risk.